(untitled) (Czech Journal of International Relations, 2024)
In capitalist countries, there has been a very lively debate in recent years about the legitimacy or illegitimacy, adequacy or inadequacy of the current form of the international monetary system. One of the main indirect motives for this general attention now being given to international monetary problems is the unfavorable development and weakened position of the reserve currencies, i.e. the US dollar and the pound sterling. The dollar and the pound form, to a greater or lesser extent, part of the monetary reserves of all capitalist countries, and concern over their prospects necessarily leads to considerations of the possibilities and reliability of the entire current international monetary system.